Comparing the effects of humic acid and oxalic acid on Pb(II) immobilization by a green synthesized nanocrystalline hydroxyapatite. (December 2021) - Wei, Wei; Han, Xuan; Shao, Yi; Xie, Wenming; Zhang, Yong; Yao, Yijun; Zhao, Wei; Han, Ruiming; Li, Shiyin; Zhang, Yong; Zheng, Chunmiao
Abstract: Dissolved organic matter (DOM) is one of the most significant parameters to affect the remediation efficiency of Pb(II) by apatites. Numerous studies chose humic substances as a surrogate of DOM to investigate its influence on Pb(II) immobilization. However, the effect of low-molecular-weight organic acids such as oxalic acid (OA), which is ubiquitous in the environment and a primary component of DOM, in immobilizing Pb(II) was still not fully understood. Herein, humic acid (HA) and OA were examined to distinguish their influence on Pb(II) immobilization by a green synthesized nanocrystalline hydroxyapatite (nHAP). Various parameters were considered to evaluate the removal performance of nHAP towards Pb(II) as affected by HA/OA. Results indicated that Pb(II) immobilization was significantly promoted in the coexistence of OA owing to the precipitation of hydroxypyromorphite (HPY) as well as PbC2 O4, but was independent on the addition sequence and slightly hindered by HA, disclosing that Pb(II) preferred to bind directly with nHAP instead of via HA. Characterization of the Pb(II) loaded solids by multiple technologies revealed that HPY was the predominant precipitate both in the absence and presence of HA, while the formation of PbC2 O4 was preferred over that of HPY in the existence of OA. X-ray photoelectron spectroscopy indicated that PbC2 O4 was the prevalent solid phase with the ratio of 62.97% after Pb(II) immobilization by nHAP in the presence of OA. These findings implied that the transformation efficiency of Pb(II) to HPY by apatites can be overestimated in the presence of OA due to the precipitation of PbC2 O4 . Graphical abstract: Image 1 Highlights: Biogenic nHAP was prepared, characterized, and tested for Pb(II) removal. HA and OA exerted different effects on Pb(II) immobilization by nHAP. OA significantly promoted Pb(II) immobilization through precipitation of PbC2 O4 . Isotherm and kinetic data were best fitted by Sips and pseudo-second-order models. Multiple techniques revealed the roles of HA/OA in Pb(II) capture.